Auto Depth Control For Underwater Remotely Operated Vehicles Using A Flexible Ballast Tank System - Mohd Aras, Mohd Shahrieel; Abdullah, Shahrum Shah; Abdul Azis, Fadilah; Mohd Zambri, Mohd Khairi; Md Basar, Mohd Farriz (Penerbit Universiti, UTeM, 2015)
-